AB0233 ATTAINING CDAI REMISSION IS THE FIRST GATEWAY TO ATTAIN BOOLEAN REMISSION. (2nd June 2020) - Yoshii, I.
Abstract : Background: Boolean remission is most stringent but most comparable remission status for the patient with rheumatoid arthritis (RA). Clinical remission evaluated with clinical disease activity index (CDAI) is also one of the most popular index for evaluation of RA treatment. These two criteria often overlap, but some are split. Objectives: Clinical significance of attaining CDAI remission before attaining Boolean remission was investigated. Methods: Patient with RA were treated in the institute since August 2010 under treat to target (T2T) strategy. In accordance with T2T, RA patients were monitored from the first consultation with parameter such as tenderness joint count (TJC), swollen joint count (SJC), patient's global assessment (PGA), evaluator's global assessment (EGA), C-reactive protein (CRP), modified Health Assessment Questionnaire (mHAQ), pain scale with visual analog scale (PS-VAS), and EuroQOL 5-dimension (EQ-5D). CDAI and Boolean are also evaluated at the same time. Radiographs of bilateral hands and feet are taken once a year from the first consultation, and the Sharp/van der Heijde Score (SHS) is measured. In patients, a group who attained CDAI remission prior to attaining Boolean remission (CDAI-R), a group who could not attain CDAI remission previously than attaining Boolean remission (CDAI-F), and a group who could not attain Boolean remission despite attaining CDAI remission (Boolean-F) were picked up and divided according to change of disease activity. Among these three groups, mean age, sex, education level, job style, anti-cyclic citrullinated polypeptide antibodies (ACPA), rheumatoid factor (RF), the CDAI score, the HAQ score, PS-VAS and quality of life index (QOL) calculated from EQ-5D were compared with each other using Mann-Whitney U-test. Boolean remission attaining rate whether CDAI remission attained was compared with chi square test. Results: Patient group configured with 255 of CDAI-R, 160 of CDAI-F, and 28 of Boolean-F. Patient who could not attain none of CDAI nor Boolean remission counted 175. In background factors at baseline, mean age, the HAQ score, and SHS of the Boolean-F were significantly older than the other groups. In the two groups of CDAI-R and CDAI-F, 28-joints disease activity score with C-reactive protein (DAS28-CRP), CDAI and PS-VAS in the CDAI-R were significantly lower than in the CDAI-F, similarly, DAS28-CRP, the CDAI score, the HAQ score, PS-VAS and QOL after Boolean remission attain were significantly higher in the CDAI-F than the CDAI-R. Sensitivity of Boolean remission when attaining CDAI remission previously before Boolean remission is 93.4%, and specificity was 52.2% (p<1.0x10 -30 ). Conclusion: Attaining CDAI remission previously is extremely important, both for attaining Boolean remission and more stable clinical course after attaining Boolean remission. CDAI remission could be the first gateway to send sustainable QOL course. Disclosure of Interests: None declared